Tout le reste n'est pas que roman... : inflexions et convergences dans la poesie française post-80 - Mendes, Ana Paula Coutinho (2014)
Does french poetry written and published after the 1980's correspond to a disruption or to a re-appropriation of certain axes of aesthetic modernity? Even if in a provisional and brief way, the reading proposed here will try to answer this question, highlighting the structuring lines regarding the literature that marks the transition between the twentieth- and the twentyfirst century.